Akibat Hukum Pembuatan Akta Oleh Notaris Di Luar Wilayah Jabatan Berdasarkan Undang-Undang Jabatan Notaris - Alamsyah R; Ahmad Rustan; Rudi Iskandar Ichlas (Jurnal Hukum Lex Generalis, 2025)
The state delegates authority to a notary as a public official to prepare authentic deeds that serve as the strongest evidence in the civil law process. Notaries in issuing deeds are based on legitimate authority including the scope of the substance of the authority regarding the scope of the authority's validity. However, in carrying out their duties, cases of Notaries still occur who exercise their authority beyond the scope of their position, which has the potential to cause legal problems and uncertainty for various interested parties. This is relevant because the validity and strength of a deed depend on the authority of the official who made it. This study aims to examine the legal implications of the preparation of deeds by Notaries carried out outside the scope of their territorial authority as regulated in the Notary Law (UUJN), as well as examine the form of legal liability that can be applied to Notaries who violate the provisions. The results of the analysis show that the deeds made by Notaries outside the scope of their authority do not meet the formal requirements required for authentic deeds according to Article 1868 of the Civil Code, so they lose their authenticity and have evidentiary value as private deeds. From an administrative law perspective, if a decision is made that is not based on legitimate authority, the legal consequence is that the decision is null and void.